Pelatihan dan pendampingan tentang strategi Kepala sekolah dalam meningkatkan kompetensi Guru bidang profesional Di SMA Primaganda Jombang - Solechan Solechan; Zahrotun Ni’mah Afif; Sunardi Sunardi; Binti Masrufa; Ainur Rofiq (An Naf'ah: Jurnal Pengabdian Masyarakat, 2023)
This community dedication describes an effort to improve the quality of education at Primaganda Jombang High School by focusing on the development of teacher competence in the professional field. Approaches used include intensive training, sustained support, and a change in the leadership strategy of the head of school. The program aims to improve learning skills, teaching skills, effective classroom management, and the motivation of teachers and students. The results of community dedication show a significant improvement in teacher competence. They have a better understanding of the subject matter and are able to apply more innovative teaching methods. More effective classroom management creates a more dynamic learning environment, which is reflected in improved student learning outcomes and reduced absences. Moreover, a more inclusive and teacher-development-oriented head of school leadership strategy has created a positive school climate. Teachers feel supported in their professional development and are more motivated. This program not only provides direct benefits to Jombang Primaganda High School but also has the potential to be adopted as a model for other schools. Investing in teacher competence development and changing leadership strategies is an important step in improving the quality of education. Continuous evaluation and sustained commitment are needed to ensure the sustainability of these positive impacts and disseminate best practices throughout the educational community. This community commitment reflects a commitment to improved education and sustainable growth at the high school level.